INFLUENCE OF WORKLOAD AND DIGITAL COMPETENCY ON PERFORMANCE OF EMPLOYEES - Tituk Indra Yusanti; Sri Suprapti (Proceeding of The International Conference on Business and Economics, 2023)
For more than a year, the Covid-19 pandemic has hit, causing many changes and giving birth to new norms and practices in the social, political, and economic order, both at the individual, community, institutional, state governance, and relations between nations. One of those affected is the office sector, but agencies are required to optimize performance without neglecting the health protocols set by the government. This study aims to determine the effect of workload and digital competence on employee performance at the Batang Regency Public Works and Spatial Planning Office. The population in this study were all employees of the State Civil Apparatus totaling 133 people. The sampling method is using a census. The data collection technique used a questionnaire and the analytical method used was multiple linear regression. The results of the analysis show that the workload has no significant positive effect on employee performance. The workload is an obligation that must be completed by employees following the specified time so that the level of workload does not affect employee performance. Digital competence has a positive and significant effect on employee performance. This finding implies that employees within the Batang Regency Public Works and Spatial Planning Office can operate digital devices.